Pengaruh Kepemimpinan Transformasional terhadap Kepercayaan dan Organizational Citizenship Behavior di Desa Preneur Sriharjo - Budi Nugroho, Anto; Subyantoro, Arief; Siswanti, Yuni (Strata Social and Humanities Studies, 2023)
This research aims to analyze and evaluate the impact of transformational leadership on Organizational Citizenship Behavior (OCB) in the Sriharjo Preneur Village community. The analysis will focus on the relationship between trust and OCB. Leadership style is a complex phenomenon consisting of three components, namely followers, leaders, and situations. How leadership is exercised is an essential factor in the growth and success of an organization. This research uses a quantitative approach, and PLS-SEM analyzes the relationship between different variables. Data was collected using a technique called simple random sampling. During the data collection stage, 92 respondents were collected, all administrators and members of Sriharjo Preneur Village. After that, the questionnaire, the research instrument, was distributed to respondents. This study found that transformational leadership had a positive and significant influence on trust, and the same results were also found for the force between transformational leadership and OCB.